Student’s Perception, Attitude and Advantage Towards the Use Of Whatsapp Mobile Learning Outside Classroom: An Indonesian Student’s Experience - Agus Budiharto; Sayu In Puja Mentari; Talullah Janna D; Kinanatul F (Peneliti.net, 2020)
Today, many institutions of higher education worldwide frequently utilize online instruction through trendy WhatsApp as representing an instant messaging application for Smartphone. The present study is aimed at introducing a mobile gadget that become useful in practices of teaching learning. The objectives of the study are to examine the student’s perception on omnipresent aspect of WhatsApp mobile learning, to examine the students’ attitude on WhatsApp mobile learning and to examine educational advantages of WhatsApp mobile learning. The participants of this study were 33 students who were all in seventh semester in English Education Study Program of Teacher Training and Education Faculty, University of Madura and pursuing Teaching Practice Program, academic session 2018-2019, in some selected government schools located in Pamekasan area when this study was conducted. The study employs mixed method, viz, by using quantitative and qualitative method since the study describes student’s experience regarding WhatsApp mobile learning. In this research, questionnaire and interviews were employed to collect data. The results reveal that omnipresent WhatsApp mobile learning is not only appealing but also useful for their education. The students’ positive attitude of WhatsApp mobile learning is emphasized in the study. Some have a preference to employ traditional learning inside classroom to WhatsApp mobile learning. However some feel disposed to keep employing WhatsApp for future teaching learning. Furthermore, WhatsApp mobile learning is not quite compatible with the have family - students hence they like better traditional teaching learning in classroom because the learning make their family life troublesome.